Pengupahan PT Sumber Izumi Mas Perkasa: UU Ketenagakerjaan Tahun 2003 dan UU Cipta Kerja Tahun 2023 Mana Yang Lebih Menguntungkan? - Amanda, Dhea; Haliza, Siti Nur; Marlina, Marlina (CV. ITTC INDONESIA, 2023)
The Job Creation Law enacted in 2020 has undergone significant changes to several labor norms, including rules on non-permanent contracts, outsourcing, the use of foreign workers, layoff mechanisms, and administrative and criminal sanctions. One of the laws affected by these changes is Law No.13 Year 2003 on Manpower. This omnibus law is a pruning of various kinds of bureaucracy in statutory regulations that can threaten the development of the country's progress. Perppu number 2 of 2022 on job creation officially replaces some articles in several labor-related laws, including Law No. 13 of 2003 on Manpower, Law No. 40 of 2004 on the National Social Security System, Law No. 24 of 2011 on the Social Security Organizing Agency, and Law No. 18 of 2017 on the Protection of Indonesian Migrant Workers. This research was conducted at PT Sumber Izumi Mas Perkasa, which is one of the companies engaged in bottled drinking water. The purpose of this research is to see how the impact of the change in law from the Manpower Law to the Job Creation Law at PT Sumber Izumi Mas Perkasa. This research uses a qualitative research method with a descriptive phenomenological approach. Qualitative research is a type of research that does not rely on quantification techniques, statistical calculations, or other techniques that use numerical measures to arrive at its conclusions. The result of this research is that PT Sumber Izumi Mas Perkasa has not fully implemented the contents of the Job Creation Law. However, it has implemented a wage system and social security for employees. This is because the company still needs time to study and deepen the Job Creation Law before it is fully implemented at PT Sumber Izumi Mas Perkasa.